Paradigms of dynamic chaos - Buts, V.A. (Вопросы атомной науки и техники, 2013)
It is shown that a condition of occurrence of regimes with chaotic behavior of dynamic systems demands more steadfast studying. In particular, it is shown that if we will take into account singular solutions the chaotic behavior will be inherent also in systems with one degree of freedom. It is shown that linear systems can generate chaotic dynamics. The question about necessity of local instability for realization of chaotic regimes is discussed.